The Atlantic Ocean, the Immigrants and the Transoceanic Exchange of the Yellow Fever. A New Perspective about the 19th Century Epidemic in Buenos Aires (1870-1871) - Rey, Nicolás Fernán (2021)
This investigation analyses the yellow fever epidemic that arrived to Buenos Aires in the year 1871. Connected with the COVID-19 pandemic that defied the globalized world, it is intended to look in the past the problems that the societies faced when the plagues arrived at their front doors. In this case, the transoceanic connections that took place until the second half of the19th century will be analyzed. The ships not only transported people, ideas and cargo, but also pathogens inside them. From the transnational approach to environmental history, the newspapers’ reports, the memories of the Buenos Aires port health commission, those of the Central Immigration Commission, as well as articles from the Spanish newspaper Eco de Alicante will be analyzed, to stablish a connection between the epidemic developed in the end of 1870 in Barcelona the one that started in Buenos Aires in 1871. It is concluded that, being these two ports attached permanently and forced to face the shortcomings above the ships, such as the overcrowding of passengers and the deficient control of the sanitary authorities, the yellow fever epidemic of Buenos Aires could have arrived from Barcelona as well and not only from Asunción, as the consulted bibliography states.